Clinical Characteristics, Risk Factors and Angiographic Profile of Patients Undergoing Coronary Angiography in A Tertiary Care Hospital - Ahsan, Mohammad Morshedul; SM, Shahidul Haque; Sultana, Surovi; Sarker, Alok Chandra; Hossain, Md. Shahadat; Siddiqui, Mohammad Khalilur Rahman; Jamil, Abu Baqar Md.; Faruq, Md. Fysal (Cardiology and Cardiovascular Medicine, 2023)
Background: In both developed and developing countries, coronary artery disease is one of the most common causes of huge mortality and morbidity. Considering the increasing burden of coronary artery disease, to control the mortality as well as morbidity of this disease, identifying risk factors, studying the clinical profile and angiographic pattern of such patients is very important. Aim of the Study: The aim of this study was to accumulate the clinical characteristics, risk factors and angiographic profile of patients undergoing coronary angiography. Methods: This prospective observational study was conducted in the department of Cardiology, Shaheed Ziaur Rahman Medical College & Hospital Bogura, Bangladesh during the period from January 2020 to June 2022. In total 165 patients undergoing coronary angiography in the mentioned hospital were enrolled in this study as study subjects. As per the inclusion criteria of this study, patients from several age groups of both genders were included as the study subjects. A predesigned questioner was used in collecting data regarding all demographic, clinical and diagnostic findings. Results: In this study, as the clinical diagnostic findings of participants UA, NSTEMI, anterior STEMI, inferior STEMI and CSA were found among 42%, 16%, 14%, 13% and 15% cases respectively. As the risk factors, DM was found in 18% cases and HTN was found in 17% cases which were noticeable. Besides these, smoking, family history and hypothyroidism were found among 10%, 2% and 1% participants respectively. Finally, in analyzing the coronary angiography findings of our study people we observed that, 35% patients were with normal coronary artery. Among a large proportion of patients, SVD was found which were in 31% (n=52) cases. Besides thes